2015
DOI: 10.1111/sum.12183
|View full text |Cite
|
Sign up to set email alerts
|

The effect of arbuscular mycorrhiza fungal propagules on the growth of subterranean clover (Trifolium subterraneum L.) under Mn toxicity in ex situ experiments

Abstract: The role of intact extraradical mycelium (ERM) as the most effective fungal propagule in the formation of the tripartite symbiosis between indigenous arbuscular mycorrhizal fungi (AMF), rhizobia and subterranean clover was investigated under conditions of Mn toxicity. ERM was previously developed in 8 L pots under greenhouse conditions by growing plants, which exhibited various levels of mycotrophicity and were tolerant to the levels of Mn in the soil used in the experiment (Silene gallica L, Lolium rigidum L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…These sources are not equally effective at producing new infection units. Indeed, colonization initiated by an intact ERM starts earlier and develop faster ( Goss and De Varennes, 2002 ; Brito et al, 2014 ; Alho et al, 2015 ) whereas the slower colonization from spores is linked to the need for germination to be initiated by signaling from the host plant ( Garg and Chandel, 2010 ). Similarly to previous observations by Brito et al (2014) , we found significant differences in wheat growth between the undisturbed and disturbed regimes, but also between the yellow-serradella and ryegrass systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sources are not equally effective at producing new infection units. Indeed, colonization initiated by an intact ERM starts earlier and develop faster ( Goss and De Varennes, 2002 ; Brito et al, 2014 ; Alho et al, 2015 ) whereas the slower colonization from spores is linked to the need for germination to be initiated by signaling from the host plant ( Garg and Chandel, 2010 ). Similarly to previous observations by Brito et al (2014) , we found significant differences in wheat growth between the undisturbed and disturbed regimes, but also between the yellow-serradella and ryegrass systems.…”
Section: Discussionmentioning
confidence: 99%
“…The scarecrow-like protein 26/nodulation signaling pathway (SCL26/NSP2) belongs to the GRAS family and has been found to facilitate mycorrhizal colonization ( Maillet et al, 2011 ; Gobbato et al, 2012 ). Given that disturbed or undisturbed ERM affects how early and fast the colonization occurs ( Goss and De Varennes, 2002 ; Brito et al, 2014 ; Alho et al, 2015 ), we also looked at the expression of the specific AMF induced phosphate transporter PhT1 Myc gene. Gene sequences were retrieved from Ensembl Plants database.…”
Section: Methodsmentioning
confidence: 99%
“…Several native leguminous plant species common to the Mediterranean region were surveyed for the presence of plant growth-promoting endophytic bacteria. Legume plants were harvested from two different sites (±65 km distance among sites) in South of Portugal, namely in an acid Cambisol (granitic origin) under natural pasture at Herdade da Mitra, at the University of Évora (38°32′ N; 08°00′ W), known for its Mn toxicity to plants, including leguminous species [19,20], and from the ridge between two rice fields damaged by salinity located at Alcácer do Sal (38°25′ N; 08°36′ W). In addition to the differences in the soil types of these sites, they also possess distinct bioclimatic conditions: Herdade da Mitra is located in inferior subhumid and inferior mesomediterranean (ombrotype/thermotype) while Alcácer do Sal is under a superior dry and superior termomediterranean [21].…”
Section: Methodsmentioning
confidence: 99%
“…The net effects of these microbes on Trifolium hosts were highly variable and depended on the host species and the source (native or introduced range) of the microbes and hosts (Shelby et al, ). Moreover, the combined effects of AMF and other microbes have been shown to interact and thus alter both the benefits received by Trifolium and PSFs (Alho, Carvalho, Brito, & Goss, ; García‐Parisi, Lattanzi, Grimoldi, Druille, & Omacini, ). Rhizobia and AMF together reduce the competitive suppression of Trifolium species by grasses (Hall, ; Thompson, Turkington, & Holl, ; Wagg, Jansa, & Stadler, ).…”
Section: Introductionmentioning
confidence: 99%